Course of symptom change during anxiety treatment: Reductions in anxiety and depression in patients completing the Coordinated Anxiety Learning and Management program. Issue 1 (30th September 2015) - Bomyea, Jessica; Lang, Ariel; Craske, Michelle G.; Chavira, Denise A.; Sherbourne, Cathy D.; Rose, Raphael D.; Golinelli, Daniela; Campbell-Sills, Laura; Welch, Stacy S.; Sullivan, Greer; Bystritsky, Alexander; Roy-Byrne, Peter; et al.
Abstract: When treating anxious patients with co-occurring depression, research demonstrates that both types of symptoms independently improve. The current analyses examined how reductions in anxiety and depression may be interrelated both during treatment, as well as over time following treatment. Participants were 503 individuals with one or more DSM-IV anxiety disorders who completed a collaborative care anxiety management program. Anxiety and depression were assessed at each treatment session (i.e., session by session data) and also at 6, 12, and 18-month post-baseline assessments (i.e., long-term outcomes data). Mediation analyses examined changes in symptoms in session by session data and long-term outcomes data. Anxiety and depression changed reciprocally in session by session data; change in anxiety mediated change in depression to a greater extent than vice versa. In the long-term outcomes data, change in anxiety mediated change in depression. However, the reverse mediation model of the long-term outcomes period revealed that accounting for changes in depression altered the effect of time on anxiety. Thus, temporal change during active treatment may share similarities with those related to maintaining gains after treatment, although differences arose in the reverse mediation models. Limitations of the methodology and implications of anxiety treatment for depression outcomes are discussed. Highlights: Examined mediation of symptom reduction during treatment delivered in primary care. Changes in anxiety mediated changes in depression during the active phase of treatment. Changes in anxiety mediated changes in depression during an 18-month follow up period. Reverse mediation model suggests complex relationships between anxiety and depression during follow up.